Clinical behavior of 203 stage II endometrial cancer cases: The impact of primary surgical approach and of adjuvant radiation therapy. Issue 6 (1st November 2001) - Sartori, E.; Gadducci, A.; Landoni, F.; Lissoni, A.; Maggino, T.; Zola, P.; Zanagnolo, V.
Abstract : The aim of this study was to verify the impact of primary surgical approach and adjuvant radiation therapy (RT) on survival, recurrence rate, and pattern of relapse in stage II endometrial cancer patients. Two hundred three subjects were retrospectively reviewed; 135 (66%) underwent simple hysterectomy (SH) and 68 (34%) radical hysterectomy (RH). Sixty-six of 111 (59%) of stage IIA and 67 of 92 (73%) of stage IIB patients underwent adjuvant radiation therapy. Actuarial survival rates for stage IIA and IIB were 86% and 74% at 5 years and 82% and 68% at 10 years, respectively. Survival rates by surgical procedure were 79% in the SH group and 94% in the RH group at 5 years and 74% and 94% at 10 years, respectively ( P < 0.05). The overall recurrence rate was 13.8% (28/203); by adjuvant treatment it was 18.6% (13/70) in the observation group and 11.3% (15/133) in the RT group. Most of the relapses were locoregional in the observation group and distant in the RT group. Survival rates by RT were not statistically different. Subjects treated with RH improved their survival compared with the SH group; the difference was significant, but randomized studies should confirm this trend. Although adjuvant RT seemed to reduce the recurrence rate, there was no significant difference in survival, and so the role of RT still needs further verification.